Презентації історії Правобережної та Лівобережної України в модерних регіонально-історичних текстах: до постановки проблеми - Новікова, Л. (Чорноморська минувшина, 2020)
Незважаючи на розвиток у сучасній історичній науці таких напрямків, як історичне краєзнавство та історична регіоналістика, недостатньо вивченим залишається специфіка історіографічної презентації українських регіонів у модерний період. У даному дослідженні здійснена спроба визначити складну структуру історіографічних інтерпретацій історії Лівобережної та Правобережної України в модерну добу, що співіснували й були проявами трансформацій суспільної ідентичності, окреслити це питання як окрему наукову проблему в галузі історичної регіоналістики. Було встановлено, що історіографічні презентації історії Правобережної та Лівобережної України у ХІХ – на початку ХХ ст. мали складну структуру. Історія Правобережжя (або його субрегіонів) включалася в контекст «західноруської» історії, історії західної частини Російської імперії, польської концепції «східних кресів», а також до парадигми національної української історії. Остання теж переживала трансформацію, зокрема, від історії Київської землі та Південно-Західної Русі, Малоросії до власне історії України. У зв’язку з цим наприкінці ХІХ ст. з’являються праці, спеціально присвячені історії «Правобережної України». Подібну еволюцію переживає і презентація історії Лівобережжя (його субрегіонів). Водночас тут була й своя специфіка, визначена тим, що це була територія колишньої Лівобережної Гетьманщини, внаслідок чого наявна така презентація історії регіону як історії полків. Водночас спостерігається тенденція до переходу на межі ХІХ-ХХ ст. до розгляду історії регіону власне як історії «Лівобережної України». Відкритим поки що залишається питання те, як історія Лівобережної України відображалася в контексті «західноруського» підходу, хоча вона і висвітлювалася в контексті пов’язаної, на наш погляд, з цим підходом обласної (земельної) концепції. Despite the development in modern historical science of such areas as historical local history and historical regional studies, the specifics of the historiographic presentation of Ukrainian regions in the modern period remains insufficiently studied. In this study, an attempt was made to determine the complex structure of historiographic interpretations of Left-Bank and Right-Bank Ukraine in modern times, which coexisted and were manifestations of transformations of social identity, to outline this issue as a separate scientific problem in the field of historical regional studies. It was found that historiographical presentations of the history of Right-bank and Left-Bank Ukraine in the XIX - early XX century had a complicated structure. The history of the Right Bank (or its subregions) was included in the context of “Western-Russian” history, the history of the western part of the Russian Empire, the Polish concept of "oriental kreses", as well as the paradigm of national Ukrainian history. The latter also experienced transformation, in particular, from the history of Kievian land and South-Western Russia, Little Russia to the history of Ukraine itself. In this regard, in the late ХІХ century, there were works specifically devoted to the history of "Right- Bank Ukraine". A similar evolution is experienced by the presentation of the history of the Left-Bank Ukraine (its subregions). At the same time, there was also its own specificity, determined by the fact that it was the territory of the former Left-Bank Hetmanate. As a result, there was such a presentation of the history of the region as the history of the Cossack regiments (as administrative territories). At the same time, there is a tendency at the edge of the XIX and XX centuries to consider the history of the region as the history of "Left-Bank Ukraine". The question of how the history of Left- Bank Ukraine was reflected in the context of the "West-Russian" concept remains open, although its reflection is present in the related regional (“oblast” or “land”) one.